Altered sugar donor specificity and catalytic activity of pteridine glycosyltransferases by domain swapping or site-directed mutagenesis - Hye-Lim Kim; Ae Hyun Kim; Mi Bi Park; Soo-Woong Lee; Young Shik Park (BMB Reports, 2013)
CY-007 and CY-049 pteridine glycosyltransferases (PGTs) thatdiffer in sugar donor specificity to catalyze either glucose orxylose transfer to tetrahydrobiopterin were studied here touncover the structural determinants necessary for the specificity.The importance of the C-terminal domain and its residues 218and 258 that are different between the two PGTs was assessed viastructure-guided domain swapping or single and dual amino acidsubstitutions. Catalytic activity and selectivity were altered in allthe mutants (2 chimeric and 6 substitution) to accept bothUDP-glucose and UDP-xylose. In addition, the wild typeactivities were improved 1.6-4.2 fold in 4 substitution mutantsand activity was observed towards another substrate UDP-Nacetylglucosaminein all the substitution mutants from CY-007PGT. The results strongly support essential role of the C-terminaldomain and the two residues for catalysis as well as sugar donorspecificity, bringing insight into the structural features of thePGTs. [BMB Reports 2013; 46(1): 37-40]